Effect of Workload Server on Server Room Temperature: An IoT-Based Monitoring - Sabam Parjuangan; Cecep Hendrik (Proceeding International Conference on Information Technology and Business, 2020)
A server was the computer device that served one or more computing devices (clients). The servers that serve client had high-speed processor specifications. Each of the service requests increased the server workload. This increasing workload logically increased the work of the processor so that the processor temperature was increasing. This article described comprehensively the changes of the server room temperature due to the increasing workload of the server. The objective of this study was finding out the effect of the server engine workload on the server room temperature. The method used in this study was the IoT-Based monitoring method. The temperature sensor was used and combined with the Node MCU connected to the website server as a tabulation of the observation data. It was designed to avoid the heat caused by external factors (e.g., humans). The sensors were placed on the server rack. The result of this study was that the increasing workload of the server did not have a significant effect on the server room temperature. The result of this study was expected to be the input for designing the server chassis and the server roomKeywords: Server, Temperature, IoT-Based Monitoring, Workload.